Results of treatment of bilateral destructive pulmonary tuberculosis patients using mini-invasive surgical interventions. - I. V. Korpusenko; Yu. F. Savenkov (Medičnì Perspektivi)
There were analyzed case-histories of patients operated on bilateral destructive pulmonary tuberculosis who underwent treatment at pulmonary-surgical unit of CI “DRCCTPA” Phthisiatria” from 2010 to 2018. Case histories of 259 patients’ were included in the study, in complex treatment of which, surgical stage of treatment was used. Analyzing direct results in 2 months after surgery, the estimation based on clinical, roentgenologic and laboratory studies by criteria of destruction cavities closure, bacterioexcretion termination and clinical stabilization of the tuberculosis process was used. In carrying out a research patients were divided into 2 groups: the main group consisted of 129 patients who underwent mini-invasive methods of surgical treatment with mini-access under the control of video-thoracoscopy (single-step or staging bilateral video-assisted lung resection – 58 patients, collapse-surgical video-assisted single-step or staging interventions – 53, staging mini-invasive pleuropneumonectomy – 18). The comparison group included 130 patients operated according to standard approaches with conventional methods. Comparison groups did not differ reliably (p>0,05) by the gender and the age, by tuberculosis forms, by disease duration, by functional parameters, by main prevalence and severity of tuberculosis. A biggest number of complications in both groups was noted after pleuropneumonectomies, lobectomies and thoracoplasty. In the comparison group postoperative complications were observed in 32 (24.6%) patients, that is 2.2 more often (p=0.002). In the main group, bronchopleural complications occurred in 8 cases (6.2%), and in the comparison group – in 16 (12.3%), that is 2 times less frequently, exacerbation of tuberculosis process was noted 3.8 times more often in patients of comparison group. Performed analysis of the nature of postoperative complications in both groups confirms the effect of traumatism of access not only on the course of the wound process, but also on the frequency of pleural, pulmonary and functional complications. A complete clinical effect in the patients of comparison group was achieved in 82 cases (63%), that is by 1.4 times less than in the main group (p<0.001). Abacillation, while maintaining destruction in one of the lungs, occurred at the time of discharge from the hospital in 12 (9.3%) patients of the main group and in 21 (16.5%) – of the comparison one. There were 3 (2.3%) patients discharging bacteria in the main group and 20 (15.4%) patients in the comparison group.